THE ROLE OF LAPAROSTOM IN THE TREATMENT OF PATIENTS WITH NECROSIS OF THE INTESTINUM AND PERITONITIS - Ярощук, Сергей Александрович; Лещишин, Ярослав Миронович; Баранов, Андрей Игоревич; Каташева, Лилия Юрьевна (Medicine in Kuzbass, 2019)
Closure of the abdominal cavity is always a difficult task, especially in emergency surgery, when there is edema of the intestine, diffuse peritonitis. Goal – the aim of the study was to assess the role of laparostomy in the treatment of patients with small bowel necrosis and peritonitis. Results. In the first group there were 166 people, in the second 32 people. Of these, 76 were men, 90 women. The average age was 62.4 ± 18.65 years. The closure of the abdominal cavity was achieved in the first group on average for 12 days, in the second for 15 days. Anterior abdominal wall was sutured in 156 patients, in 10 patients only the skin was sutured, and in the future they needed surgical treatment for postoperative ventral hernias. Findings. The study showed that when the abdominal closure is performed under tension of the tissues of the anterior abdominal wall, the creation of a laparostomy helps to prevent the development of abdominal compartment syndrome with its systemic complications. The overlap of laparostoma prevented tearing of the tissues of the anterior abdominal wall. Conducting planned rehabilitation laparotomy allowed to control the state of the small intestine stumps with the creation of an anastomosis in a delayed manner.